The derivation of urban design principles in Malay-Islamic town of Kuala Terengganu - Nurul Syala Abdul Latip; Harun N.Z.; Abdullah A.; Ibrahim M. (Malaysian Institute Of Planners, 2024)
Indexed by WOS/ Scopus